The efficacy and safety of exercise and physical activity on psychosis: A systematic review and meta-analysis - Ziebart, Christina; Bobos, Pavlos; MacDermid, Joy C.; Furtado, Rochelle; Sobczak, Daniel J.; Doering, Michele (Frontiers in Psychiatry, 2022)
Background Treatment of psychosis typically focuses on medication, but some of these medications can have unintended side effects, exercise has global health benefits, with minimal side effects. The purpose of this systematic review and meta-analysis is to investigate the effectiveness and safety of exercise and physical activity on psychotic symptoms, in people with psychosis when compared to usual care, in a hospital setting. Methods A systematic electronic search of the literature was performed in June 2022, in PubMed, Scopus, and PsychINFO with no date restrictions. We included randomized trials (RCTs) with patients with psychosis that received an exercise intervention within a hospital setting. The primary outcome of interest was Positive and Negative Symptom Severity Scale (PANSS) overall score. Secondary outcomes were adverse or serious adverse events. Results A total of 24 trials were included in this systematic review, with 9 included in the meta-analysis, including 1,426 participants. Aerobic had more pronounced effects when compared to usual care in PANSS positive (−0.23, 95% CI −0.53 to 0.07), negative (−0.38, 95% CI −0.65 to −0.10), general (−0.42, 95% CI −0.71 to −0.13) and overall scores (−0.25, 95% CI −0.52 to 0.03). Yoga when compared to usual care had no difference in PANSS subscale and overall scores. We found no difference on relapsing of psychiatric symptoms or somatic hospitalization when we compared aerobic or yoga to usual care (Risk Ratio, 1.12 95% CI 0.44–2.81). Conclusion Aerobic activity as an exercise modality in a hospital setting can be effective in decreasing negative and general psychosis symptom severity scores compared to usual care, however, it was uncertain if the effects were clinically important. More trials are needed to confirm the clinically benefit of aerobic exercise. Systematic Review Registration [https://www.crd.york.ac.uk/prospero/], identifier [CRD42021224997].